Overprescribing iron tablets to elderly people in Sweden. Issue 6196 (20th October 1979) - Reizenstein, P; Ljunggren, G; Smedby, B; Agenäs, I; Penchansky, M
Abstract : Iron should not be prescribed to middle-aged men or older women with anaemia unless the possibility that the iron deficiency is caused by a gastrointestinal tumour has been considered. Thus the prescribing of iron to elderly people was investigated by studying four different prescription statistics and by reviewing records. Over one in 10 women aged over 65 were prescribed iron tablets. Men and women in the oldest age groups were prescribed iron most frequently. The reasons for prescribing iron were examined at a rural health centre. Out of 327 records of patients who were prescribed iron during 1975, 157 were randomly selected and reviewed. Only 18 out of 48 (38%) patients aged 45-75 (men) and 55-75 (women) and 29 out of 109 (27%) aged over 75 years had probable or possible iron-deficiency anaemia as established from the records. Only nine (19%) of the younger patients had a plausible reason for the anaemia other than a bleeding tumour. Ten (9%) of the older patients were considered to be inoperable cases. Thus, according to the records, only 18 (17%) of the patients over 75 years and nine (19%) of those in the younger age group have been prescribed iron. About 70% of all the patients were considered not to have iron deficiency; 7% had had iron deficiency previously, and 20% probably had anaemia as a result of chronic disease; for 43% no real reason for the iron prescription could be found in the record. Thus it is concluded that iron is overprescribed in Sweden, particularly for elderly people. It should not be prescribed until the possibility of a bleeding gastrointestinal tumour has been excluded.